Creative Communications on Tiktok: Construction of the Ministry of Health's Communication Innovation in COVID-19 Education in Indonesia - Nurdin, Ali; Rahmadani, Desy (Proceedings of International Conference on Da'wa and Communication, 2021)
The Ministry of Health of the Republic of Indonesia created a TikTok account @kemenkesri to educate the public about COVID-19. The purpose of this study is to describe the construction of creativity and communication innovation on Tiktok social media in preventing COVID-19. This study uses a constructivist approach to the type of analysis of the framing model of Robert N. Entman. Data was collected through TikTok video content documentation and analyzed with Robert N. Entman's framing framework. The results of the study describe that define problems constructed by the TikTok account @kemenkesri using simple, popular sentences, and according to the public's niche. Diagnose causes is constructed using examples of realities that are often present in life during the COVID-19 pandemic. Make moral judgment using sentences that are relevant to the mood of the audience. Treatment recommendations are constructed using sentences that direct an action that can be taken by the public. The key to successful communication on TikTok Social media is creativity and innovation that is carried out continuously to win the hearts of netizens.